Personalization dimensions: A conceptual model for personalized information systems - Reis, José Luís (2014)
Personalization is the adjustment of an information system to the preferences or needs of a user. Personalization can contribute to the improvement of customer relationship or of organizationalefficiency. This article presents a conceptual framework that addresses several personalization issues, such as: personalization levels; implementation levels; personalization dimensions; levels of personalization;levels of implementation and system integration of personalization with personalization dimensions.Based in a practical application, thearticle also proposesrecommendationsto Information Systems Technologies (IST) professionals involved in decisions, regarding the developmentof personalization dimensions in personalized applications.